Leptospirosis in French Polynesia: 11 years of surveillance data, 2007–2017. (May 2019) - Bouscaren, N.; Benoit de Coignac, C.; Lastère, S.; Musso, D.; Teissier, Y.; Formont, J.; Chaix, F.; Giard, M.
Abstract: Leptospirosis is a worldwide zoonosis with higher incidence in tropical areas and is a neglected disease in the Pacific region. French Polynesia (FP) is a French overseas territory located in the South Pacific. Data on the epidemiology in FP are scarce. In this study, we describe our understanding of leptospirosis epidemiology in FP and discuss the prospects concerning this disease and its surveillance to better address preventive actions. We report 11 years of surveillance data between 1 January 2007 and 31 December 2017. Over the study period, 1356 confirmed and probable leptospirosis cases were reported. The mean annual incidence rate was 46.0 (95% confidence interval, 43.6–48.5) cases per 100 000 inhabitants. We registered 864 (63.7%) hospitalizations; of these, at least 270 (19.9%) were in the intensive care unit, and 24 patients (1.8%) died. Even if the incidence of leptospirosis is lower in FP compared to most of other Pacific countries and territories, our data confirm that the disease is highly endemic in FP. Despite all the preventive measures taken, leptospirosis remains a major public health concern in FP, thus highlighting the need to maintain intensive leptospirosis surveillance, medical staff training and provision of information to the general population.